What drives the vulnerability of pastoralists to global environmental change? A qualitative meta-analysis. (July 2016) - López-i-Gelats, Feliu; Fraser, Evan D.G.; Morton, John F.; Rivera-Ferre, Marta G.
Highlights: A qualitative meta-analysis was conducted to explore patterns across the literature. Six different pathways of vulnerability followed by pastoralists were identified. The vulnerability of pastoralism is co-produced by climate and non-climate drivers. The livelihood options of pastoralists are generally becoming narrower. Abstract: The long-term viability of pastoralism has been a constant theme for discussions. The progress of knowledge on the sustainability of pastoralism under global environmental change has been notable in the last years. To better characterize this vulnerability, we have examined the existing scientific knowledge about the three dimensions of vulnerability, being exposure illustrated by the existing climate trends and non-climate transformations, sensitivity by the impacts of these on pastoral resources and pastoral land conversions, and adaptation by the adaptation strategies developed by the pastoral communities. A qualitative meta-analysis was conducted to explore patterns and trends across the literature. From this, six different pathways of vulnerability being followed by pastoral communities were identified: Encroachment, Re-greening, Customary, Polarization, Communal and No-alternative. The results point that the livelihood options of pastoralists are generally becoming narrower. Four major forces are identified as exerting determinant influence on the co-production of the vulnerability of pastoralism: (i) the double exposure to climate and non-climate transformations, (ii) the persistence of unfavorable development policies, (iii) the great vitality of adaptation, and (iv) the multifaceted role of markets. We point that it is crucial to distinguish between the component of vulnerability inherent in any economic activity devoted to the use of natural resources, which is the usual business of pastoralism, and the component of vulnerability linked to external forces that disturb the usual working of the pastoral production strategies.